In vivo monitoring of urea cycle activity with 13C-acetate as a tracer of ureagenesis - Opladen, Thomas; Lindner, Martin; Das, Anibh M.; Marquardt, Thorsten; Khan, Aneal; Emre, Sukru H.; Burton, Barbara K.; Barshop, Bruce A.; Böhm, Thea; Meyburg, Jochen; Zangerl, Kathrin; Mayorandan, Sebene; et al. (Molecular genetics and metabolism, 2016)
Background - The hepatic urea cycle is the main metabolic pathway for detoxification of ammonia. Inborn errors of urea cycle function present with severe hyperammonemia and a high case fatality rate. Long-term prognosis depends on the residual activity of the defective enzyme. A reliable method to estimate urea cycle activity in-vivo does not exist yet. The aim of this study was to evaluate a practical method to quantify 13C-urea production as a marker for urea cycle function in healthy subjects, patients with confirmed urea cycle defect (UCD) and asymptomatic carriers of UCD mutations. - Methods - 13C-labeled sodium acetate was applied orally in a single dose to 47 subjects (10 healthy subjects, 28 symptomatic patients, 9 asymptomatic carriers). - Results - The oral 13C-ureagenesis assay is a safe method. While healthy subjects and asymptomatic carriers did not differ with regards to kinetic variables for urea cycle flux, symptomatic patients had lower 13C-plasma urea levels. Although the 13C-ureagenesis assay revealed no significant differences between individual urea cycle enzyme defects, it reflected the heterogeneity between different clinical subgroups, including male neonatal onset ornithine carbamoyltransferase deficiency. Applying the 13C-urea area under the curve can differentiate between severe from more mildly affected neonates. Late onset patients differ significantly from neonates, carriers and healthy subjects. - Conclusion - This study evaluated the oral 13C-ureagenesis assay as a sensitive in-vivo measure for ureagenesis capacity. The assay has the potential to become a reliable tool to differentiate UCD patient subgroups, follow changes in ureagenesis capacity and could be helpful in monitoring novel therapies of UCD.
Published online 2015
Im Titel ist die Zahl "13" hochgestellt
Gesehen am 07.07.2020